Subgel-phase formation of membranes of ether-linked phosphatidylcholines. (September 2021) - Goto, Masaki; Sawaguchi, Hiroshi; Tamai, Nobutake; Matsuki, Hitoshi
Graphical abstract: Highlights: Membranes of ether-linked phosphatidylcholines undergo the subtransition. The subtransition shows small thermodynamic quantities with no thermal hysteresis. Membranes of ether- and ester-linked PCs form structurally different subgel phase. Difference in linkage type provides a significant effect on the subgel phase. Abstract: The formation of subgel (so-called hydrated crystal) phase of membranes of ether-linked phospholipids, dialkylphosphatidylcholines containing linear saturated alkyl chain (C n = 14, 16 and 18), was examined under atmospheric and high pressure. The results of differential scanning calorimetry in 50 wt% aqueous ethylene glycol solution and water showed that these PC membranes undergo the subtransition from the subgel phase to the gel phase at a low temperature with or without the thermal pretreatment of lipid samples called annealing. The subtransition in water was clearly observed by light-transmittance measurements under high pressure and the transition temperature increased by applying pressure. The temperature-pressure phase diagrams and the thermodynamic quantities of the subtransition were obtained from the phase-transition data and compared with those of membranes of ester-linked phospholipids, diacylphosphatidylcholines. The phase diagrams indicated that all gel phases of the ether-linked PC membranes exist as stable phases while parts of the gel phases of the ester-linked PC membranes are metastable. The subtransition temperatures of the ether-linked PC membranes were lower than those of the ester-linked PC membranes by more than 10 °C and the corresponding thermodynamic quantities were extremely small. Further, it was revealed by high-pressure fluorometry that the difference in subgel phase between ether- and ester-linked PC membranes results from their phase structures: the nonbilayer interdigitated structure is maintained after the conversion from the gel phase to the subgel phase in the ether-linked PC membranes whereas the ester-linked PC membranes form the bilayer subgel phase with staggered structure.